OUTLINE OF A GENERAL THEORY OF SYSTEMIC CONSTITUCIONALISM FOR WORLD SOCIETY - Tonet, Fernando; Nunes de Souza, Matheus Figueiredo (Revista Eletrônica Direito e Política, 2020)
The present article aims to present to academic community the outline of a general theory of systemic constitutionalism. The method used was the functionalist, based on Niklas Luhmann’s theory of autopoietic systems. The instrumental (technical) research procedures used were the literature review, documentary material, categories and operational concepts. The preliminary conclusions were that the theory of systemic constitutionalism has a greater cognitive opening, enabling new observations regarding the reflections produced until then, since it does not work with a specific leve lof constitutionality, but with multiple levels. KEYWORDS: Communication. Constitutionalism. Human rights. Systems theory.